Safety and Efficacy of Pirfenidone in Advanced Idiopathic Pulmonary Fibrosis: A Nationwide Post-Marketing Surveillance Study in Korean Patients - Chung, Man Pyo (Adv Ther, 2020)
AIM: The efficacy and safety of pirfenidone have been previously demonstrated in patients with mild-to-moderate idiopathic pulmonary fibrosis (IPF). However, the effect of pirfenidone in patients with advanced IPF remains unclear. Here, we investigated the effects of pirfenidone against advanced IPF in a real-world setting. METHODS: A prospective nationwide post-marketing study was conducted on 258 patients from 10 Korean institutions. Patients with a predicted forced vital capacity (FVC) less than 50% or a diffusing capacity of the lung for carbon monoxide (DLco) less than 35% at baseline were classified as the advanced IPF group. RESULTS: Of 219 patients included in the analysis, the majority were male (76.3%); the mean age was 67.3 years, and the advanced group accounted for 17.8% of the patients. The median treatment duration was 298 days. Among the subjects, 86.3% experienced adverse events (AEs), of which a decreased appetite (32.4%) and a photosensitivity reaction (13.7%) were the most frequent. The incidence of AEs was similar between the advanced and non-advanced groups (92.3% vs. 85.0%, respectively; p = 0.229). Although the overall discontinuation rate was higher in the advanced group than in the non-advanced group (74.4% vs. 50.0%, respectively; p = 0.006), the percentages of the patients who discontinued treatment as a result of AEs were similar in both groups (20.5% vs. 23.3%, respectively; p = 0.704). In all patients, the rates of decline in the predicted FVC and DLco over 48 weeks were − 4.3 ± 1.3% and − 4.4 ± 1.7%, respectively. There was no between-group difference in the rate of lung function decline. CONCLUSIONS: Pirfenidone used for the treatment of patients with IPF in a real-world setting was well tolerated, with an acceptable safety profile and a consistent therapeutic effect, regardless of the disease severity. TRIAL REGISTRATION: ClinicalTrials.gov NCT03761082; the trial was retrospectively registered on December 3, 2018. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12325-020-01328-8) contains supplementary material, which is available to authorized users.